Kinematics of the anthropoid os centrale and the functional consequences of scaphoid-centrale fusion in African apes and hominins. Issue 114 (January 2018) - Orr, Caley M.
Abstract: In most primates, the os centrale is interposed between the scaphoid, trapezoid, trapezium, and head of the capitate, thus constituting a component of the wrist's midcarpal complex. Scaphoid-centrale fusion is among the clearest morphological synapomorphies of African apes and hominins. Although it might facilitate knuckle-walking by increasing the rigidity and stability of the radial side of the wrist, the exact functional significance of scaphoid-centrale fusion is unclear. If fusion acts to produce a more rigid radial wrist that stabilizes the hand and limits shearing stresses, then in taxa with a free centrale, it should anchor ligaments that check extension and radial deviation, but exhibit motion independent of the scaphoid. Moreover, because the centrale sits between the scaphoid and capitate (a major stabilizing articulation), scaphoid-centrale mobility should correlate with scaphocapitate mobility in extension and radial deviation. To test these hypotheses, the centrale's ligamentous binding was investigated via dissection in Pongo and Papio, and the kinematics of the centrale were quantified in a cadaveric sample of anthropoids ( Pongo sp., Ateles geoffroyi, Colobus guereza, Macaca mulatta, and Papio anubis ) using a computed-tomography-based method to track wrist-bone motion. Results indicate that the centrale rotates freely relative to the scaphoid in all taxa. However, centrale mobility is only correlated with scaphocapitate mobility during extension in Pongo —possibly due to differences in overall wrist configuration between apes and monkeys. If an extant ape-like wrist characterized early ancestors of African apes and hominins, then scaphoid-centrale fusion would have increased midcarpal rigidity in extension relative to the primitive condition. Although biomechanically consistent with a knuckle-walking hominin ancestor, this assumes that the trait evolved specifically for that biological role, which must be squared with contradictory interpretations of extant and fossil hominoid morphology. Regardless of its original adaptive significance, scaphoid-centrale fusion likely presented a constraint on early hominin midcarpal mobility.